Clinical spectrum of the pentanucleotide repeat expansion in the RFC1 gene in ataxia syndromes. (24th November 2020) - Gisatulin, Maria; Dobricic, Valerija; Zühlke, Christine; Hellenbroich, Yorck; Tadic, Vera; Münchau, Alexander; Isenhardt, Klaus; Bürk, Katrin; Bahlo, Melanie; Lockhart, Paul J.; Lohmann, Katja; Helmchen, Christoph; et al.
Abstract : Objective: To determine the clinical significance of an intronic biallelic pentanucleotide repeat expansion in the gene encoding replication factor C subunit 1 ( RFC1 ) in patients with late-onset cerebellar ataxia, neuropathy, and vestibular areflexia syndrome (CANVAS), in patients with other ataxias, and in healthy controls by comprehensive genetic analyses. Methods: In this case-control study, we included 457 individuals comprising 26 patients with complete or incomplete CANVAS, 70 patients with late-onset cerebellar ataxia, 208 healthy controls, and 153 individuals from 39 multigenerational families without ataxia to determine repeat stability. All 96 patients were screened for the repeat expansion by duplex PCR. To further characterize the repeat type and lengths, we used fragment length analysis, repeat-primed PCR, Sanger sequencing, and Southern blotting. Expression of RFC1 and the neighboring gene WDR19 were determined by quantitative PCR. Results: Massive biallelic pentanucleotide expansions were found in 15/17 patients with complete CANVAS (88%), in 2/9 patients with incomplete CANVAS (22%), in 4/70 patients with unspecified, late-onset cerebellar ataxia (6%), but not in controls. In patients, the expansion comprised 800–1, 000 mostly AAGGG repeats. Nonmassively expanded repeat numbers were in the range of 7–137 repeats and relatively stable during transmission. Expression of RFC1 and WDR19 were unchanged and RFC1 intron retention was not found. Conclusions: A biallelic pentanucleotide repeat expansion is a frequent cause of CANVAS and found in a considerable number of patients with an incomplete clinical presentation or other forms of cerebellar ataxia. The mechanism by which the repeat expansions are causing disease remains unclear and warrants further investigations.